2015
DOI: 10.1371/journal.pone.0119178
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis of Buffalo (Bubalus bubalis) NOD1 and NOD2 Receptors and Their Functional Role in In-Vitro Cellular Immune Response

Abstract: Nucleotide binding and oligomerization domain (NOD)-like receptors (NLRs) are innate immune receptors that recognize bacterial cell wall components and initiate host immune response. Structure and function of NLRs have been well studied in human and mice, but little information exists on genetic composition and role of these receptors in innate immune system of water buffalo—a species known for its exceptional disease resistance. Here, a comparative study on the functional domains of NOD1 and NOD2 was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Studies have suggested that NOD2 participates in cell apoptosis by activating the NF-κB signaling pathway in many diseases. [16][17][18][19] Thus, we considered that NOD2 may modulate the NF-κB pathway in CLL. In addition, the STING website was used to predict the protein−protein interaction network among the top 20 differentially expressed genes, and the results revealed that NOD2 had a close relation with p53 and Bcl-2 (Figure 1D).…”
Section: Nod2 Is Involved In Cll Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that NOD2 participates in cell apoptosis by activating the NF-κB signaling pathway in many diseases. [16][17][18][19] Thus, we considered that NOD2 may modulate the NF-κB pathway in CLL. In addition, the STING website was used to predict the protein−protein interaction network among the top 20 differentially expressed genes, and the results revealed that NOD2 had a close relation with p53 and Bcl-2 (Figure 1D).…”
Section: Nod2 Is Involved In Cll Developmentmentioning
confidence: 99%
“…[28] Studies have suggested a role for NOD2 in the regulation of the NF-κB signaling pathway in many diseases. [17][18][19]29] NOD2 significantly activates the NF-κB signaling pathway and enhances antibacterial defenses, thereby increasing the expression of pro-inflammatory cytokines and defensins after stimulation with Escherichia coli. [24] Moreover, in our study, NOD2 silencing or inhibition of the NF-κB signaling pathway contributes to an elevation in ADR accumulation in CLL cells.…”
Section: Silencing Nod2 or Inhibiting The Nf-κb Signaling Pathway Pro...mentioning
confidence: 99%